Pengaruh Kedisiplinan dan Kompensasi Terhadap Kinerja Pegawai di MTS Manbaul Hikam Tegalsiwalan Kabupaten Probolinggo - Ngatimun Ngatimun; Hermanto Hermanto; Ahmad Supaidi (Ecobuss, 2016)
The purpose of this research is to know how big the influence of discipline and compensation on employee performance and variable which influence more dominant to employee performance that exist in Mts Manbaul Hikam Tegalsiwalan Probolinggo, type of quantitative descriptive research with sampling technique using total population (25 respondents) and hypothesis test Using t test and F test (α 0,05) with multiple linear regression analysis. The result of the research shows the independent variable (X1) Discipline, independent variable (X2) Compensation affects collectively on the dependent variable (Y) Employee Performance, and the discipline variable has more dominant influence than the compensation variable. This will pay attention to the leadership of the Mts Manbaul Hikam Institute which is related to the compensation of the employees in order to improve its performance. Keywords: Discipline, Compensation and Performance